A Framework for Developing Information Requirements for Built Asset Management Based on Organisational Sustainability Objectives - Dong, Yujie (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)